Preparation method and application of catalyst
The method of preparing Fe nanoparticles through zinc-based organic frameworks solves the problem of poor contact between the water electrolytic catalyst and the carbon support, improves the anti-reverse performance of the fuel cell, and extends the service life of the battery.
Patent Information
- Application Number
- CN202411121968.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-13
AI Technical Summary
In existing fuel cells, the water electrolytic catalyst has poor contact with the carbon support, resulting in catalyst corrosion during reverse pole and affecting battery performance.
The zinc-based organic framework is used for high-temperature pyrolysis to form a carbonized framework, and ferric chloride, alcohol solvent and dicyandiamide are added to a nitrogen atmosphere to generate Fe nanoparticles through heat treatment to form a nanofoam structure, and increase the specific surface area of the carbonized framework and conductivity to improve the anti-reverse properties of the catalyst.
The close combination of Fe nanoparticles and carbon support is achieved, the catalyst's anti-reverse performance is improved, the battery life is extended, and the corrosion risk of carbon support is reduced.
Smart Images

Figure CN119133480A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fuel cell, and more particularly to a catalyst for a fuel cell. Background Art
[0002] Proton exchange membrane fuel cells are mainly composed of membrane electrodes (including diffusion layers, catalyst layers and proton exchange membranes), bipolar plates and sealing materials. The reaction gas is guided by the polar plates through the gas diffusion layer to the three-phase junction for reaction. During the operation of the stack, water flooding or gas supply failure will lead to insufficient gas supply, resulting in reaction gas starvation. In particular, for the battery anode, this phenomenon will lead to more severe effects.
[0003] At the battery anode, when hydrogen starvation occurs, the monolithic cell that should have generated current cannot effectively carry out the HOR reaction due to insufficient hydrogen supply. The voltage of the monolithic cell is negative at this time, and reverse polarity occurs. When reverse polarity occurs, the anode potential of the monolithic cell will increase under the influence of the entire battery stack, and the abnormal anode potential will cause water electrolysis and carbon corrosion reactions in the monolithic cell. The occurrence of carbon corrosion reaction (COR) will cause irreversible damage such as agglomeration of Pt particles and surface deformation in the anode catalyst layer. At the same time, the GDL and flow field plate will also be corroded to cause thinning and perforation. Usually, because the rate of water electrolysis reaction (OER) is greater than COR, the continued progress of OER will suppress the reverse voltage and produce a water electrolysis platform, so that it will not cause a violent carbon corrosion reaction due to further development.
[0004] Due to the above problems, when the reverse polarity occurs, it is crucial to extend the water electrolysis time as much as possible to provide the required current for the effect of the reverse polarity. Since Pt itself has low OER catalytic activity, adding a water electrolysis catalyst (also known as an anti-reverse catalyst in the industry) is considered to be an efficient and feasible method.
[0005] The anode catalyst prepared by the conventional method is to add the water electrolysis catalyst directly into the Pt / C catalyst slurry, which has poor dispersion effect, low specific surface area, and some carbon carriers are not in good contact with the water electrolysis catalyst. The carbon carrier that is not in good contact with the water electrolysis catalyst cannot be protected during the reverse polarity process and will be directly corroded. Summary of the invention
[0006] The embodiments of the present application provide a method for preparing a catalyst and an application thereof to solve the technical problem of poor contact between a water electrolysis catalyst and a carbon carrier.
[0007] In a first aspect, an embodiment of the present application provides a method for preparing a catalyst, the method for preparing the catalyst comprising the following steps:
[0008] Providing a zinc-based metal organic framework, and performing high-temperature pyrolysis on the zinc-based metal organic framework under the protection of an inert gas to obtain a carbonized framework;
[0009] Adding the carbonized skeleton into hydrochloric acid and dispersing it evenly to obtain a first dispersion;
[0010] Adding ferric chloride, an alcohol solvent and dicyandiamide to the first dispersion and dispersing them evenly to obtain a second dispersion;
[0011] The second dispersion is heat-treated in a mixed atmosphere of hydrogen and inert gas, the carbonized skeleton is nitrogen-doped and Fe nanoparticles are generated on the carbonized skeleton to obtain the catalyst.
[0012] In some embodiments of the present application, the temperature of the high temperature pyrolysis is 900-1000°C.
[0013] In some embodiments of the present application, the high temperature pyrolysis time is 1.5 to 2.5 hours.
[0014] In some embodiments of the present application, the concentration of the hydrochloric acid is 10% to 20%.
[0015] In some embodiments of the present application, the solid content of the first dispersion is 18% to 22%.
[0016] In some embodiments of the present application, in the second dispersion, the mass ratio of ferric chloride to hydrochloric acid is 1:4-6; and / or,
[0017] In the second dispersion, the mass ratio of ferric chloride to dicyandiamide is 1:5-10; and / or,
[0018] In the second dispersion, the mass ratio of ferric chloride to alcohol solvent is 1:2.5-3.
[0019] In some embodiments of the present application, the temperature of the heat treatment is 900-1000° C.; and / or,
[0020] The heat treatment time is 4 to 6 hours.
[0021] In a second aspect, an embodiment of the present application provides a catalyst slurry, wherein the catalyst slurry comprises the catalyst described in any embodiment of the first aspect, nafion and isopropanol.
[0022] In a third aspect, an embodiment of the present application provides a membrane electrode, wherein the anode catalyst layer of the membrane electrode is prepared by the catalyst slurry described in any embodiment of the second aspect.
[0023] In a fourth aspect, an embodiment of the present application provides a fuel cell, comprising the membrane electrode as described in any embodiment of the third aspect.
[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0025] The preparation method of the catalyst provided in the embodiment of the present application uses a carbonized skeleton with abundant loading sites as a matrix, and prepares Fe nanoparticles in situ, so that the Fe nanoparticles can be firmly loaded on the carbonized skeleton and have good contact with the carbonized skeleton. In addition, the present application adds dicyandiamide as a foaming agent when forming Fe nanoparticles, so that the carbonized skeleton forms a nano foam network structure, expands the specific surface area of the carbonized skeleton, and can form more loading sites, which is conducive to better contact between Fe nanoparticles and the carbonized skeleton; at the same time, dicyandiamide also nitrogen-doped the carbonized skeleton, so that the conductivity of the carbonized skeleton increases, which enables Fe nanoparticles to more effectively protect the carbonized skeleton at high potential. The catalyst prepared by the present application has a Fe nanoparticle tightly combined with a carbon carrier and good dispersibility, and has excellent anti-reverse polarity performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0028] Figure 1 The polarization curves of Example 1, Example 2, and Comparative Example are shown in FIG. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0030] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0032] Existing water electrolysis catalysts have the technical problem of poor contact with carbon supports.
[0033] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0034] In a first aspect, an embodiment of the present application provides a method for preparing a catalyst, the method for preparing the catalyst comprising the following steps:
[0035] S1: providing a zinc-based metal organic framework, and performing high-temperature pyrolysis on the zinc-based metal organic framework under the protection of an inert gas to obtain a carbonized framework;
[0036] S2: adding the carbonized skeleton into hydrochloric acid and dispersing it evenly to obtain a first dispersion;
[0037] S3: adding ferric chloride, an alcohol solvent and dicyandiamide to the first dispersion and dispersing them uniformly to obtain a second dispersion;
[0038] S4: heat-treating the second dispersion in a mixed atmosphere of hydrogen and inert gas, nitrogen-doping the carbide skeleton and generating Fe nanoparticles on the carbide skeleton to obtain the catalyst.
[0039] It is easy to understand that after the zinc-based metal organic framework is pyrolyzed, its organic matter will be carbonized to form a carbonized skeleton, and the originally occupied sites can be replaced by iron ions, so that the iron ions can be better dispersed on the carbonized skeleton.
[0040] It is easy to understand that the reason why the present application uses a zinc-based metal-organic framework instead of other non-zinc-based metal-organic frameworks is that the zinc in the zinc-based metal-organic framework can be volatilized and burned at high temperatures, while the metal ions of other non-zinc-based metal-organic frameworks are not easy to volatilize. For example, if a manganese-based or copper-based metal-organic framework is used, an acid washing step is required to remove the manganese ions or copper ions.
[0041] In step S3, dicyandiamide acts as a foaming agent to form a nano-foam network structure on the carbonized skeleton, which is conducive to uniform loading of Fe nanoparticles thereon; dicyandiamide also nitrogen-dopes the carbonized skeleton.
[0042] The present application uses a carbonized skeleton with abundant loading sites as a matrix to prepare Fe nanoparticles in situ, so that the Fe nanoparticles can be firmly loaded onto the carbonized skeleton and have good contact with the carbonized skeleton. In addition, the present application adds dicyandiamide as a foaming agent when forming Fe nanoparticles, so that the carbonized skeleton forms a nano foam network structure, expands the specific surface area of the carbonized skeleton, and can form more loading sites, which is conducive to better contact between the Fe nanoparticles and the carbonized skeleton; at the same time, dicyandiamide also nitrogen-doped the carbonized skeleton, so that the conductivity of the carbonized skeleton increases, which enables the Fe nanoparticles to more effectively protect the carbonized skeleton at high potential. The catalyst prepared by the present application has Fe nanoparticles tightly combined with the carbon carrier and good dispersibility, and has excellent anti-reverse polarity performance.
[0043] In addition, the present application uses a zinc-based metal organic framework for high-temperature pyrolysis. After the zinc-based metal organic framework is pyrolyzed at high temperature, it can be used directly without washing away metal ions, and the method is simple.
[0044] In some embodiments of the present application, the temperature of the high temperature pyrolysis is 900-1000°C.
[0045] In some embodiments of the present application, the high temperature pyrolysis time is 1.5 to 2.5 hours.
[0046] As an example, the temperature of the high temperature pyrolysis may be 900°C, 920°C, 940°C, 960°C, 980°C, or 1000°C.
[0047] In some embodiments of the present application, the concentration of the hydrochloric acid is 10% to 20%.
[0048] As an example, the concentration of the hydrochloric acid may be 10%, 12%, 14%, 16%, 18%, or 20%.
[0049] In some embodiments of the present application, the solid content of the first dispersion is 18% to 22%.
[0050] As an example, the solid content of the first dispersion may be 18%, 19%, 20%, 21%, or 22%.
[0051] In some embodiments of the present application, in the second dispersion, the mass ratio of ferric chloride to hydrochloric acid is 1:4-6; and / or,
[0052] In the second dispersion, the mass ratio of ferric chloride to dicyandiamide is 1:5-10; and / or,
[0053] In the second dispersion, the mass ratio of ferric chloride to alcohol solvent is 1:2.5-3.
[0054] As an example, in the second dispersion, the mass ratio of ferric chloride to hydrochloric acid may be 1:4, 1:4.5, 1:5, 1:5.5, or 1:6.
[0055] As an example, in the second dispersion, the mass ratio of ferric chloride to dicyandiamide may be 1:5, 1:6, 1:7, 1:8, 1:9, or 1:10.
[0056] As an example, in the second dispersion, the mass ratio of ferric chloride to alcohol solvent may be 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, or 1:3.
[0057] In some embodiments of the present application, the temperature of the heat treatment is 900-1000° C.; and / or,
[0058] The heat treatment time is 4 to 6 hours.
[0059] As an example, the temperature of the heat treatment may be 900°C, 920°C, 940°C, 960°C, 980°C, or 1000°C.
[0060] As an example, the heat treatment time may be 4.5 h, 5 h, 5.5 h, or 6 h.
[0061] In a second aspect, an embodiment of the present application provides a catalyst slurry, wherein the catalyst slurry comprises the catalyst described in any embodiment of the first aspect, nafion and isopropanol.
[0062] It is easy to understand that the preparation of catalyst slurry using platinum-carbon as a catalyst is a mature process in the art, and the present application also belongs to a carbon-supported catalyst, and the dispersibility, film-forming ability, and fluidity of the corresponding slurry are similar. Therefore, those skilled in the art can refer to the known platinum-carbon catalyst slurry preparation process and reasonably set the ratio of the various components of the catalyst slurry described in the present application.
[0063] The catalyst slurry is realized based on a catalyst prepared by the method described in any embodiment of the first aspect. The specific implementation of the catalyst slurry can refer to the above embodiments and common knowledge in the field. Since the catalyst slurry adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0064] In a third aspect, an embodiment of the present application provides a membrane electrode, wherein the anode catalyst layer of the membrane electrode is prepared by the catalyst slurry described in any embodiment of the second aspect.
[0065] The membrane electrode is realized based on the catalyst slurry described in any embodiment of the second aspect. The specific implementation of the membrane electrode can refer to the above embodiments and common knowledge in the field. Since the membrane electrode adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0066] In a fourth aspect, an embodiment of the present application provides a fuel cell, comprising the membrane electrode as described in any embodiment of the third aspect.
[0067] The fuel cell is realized based on the membrane electrode described in any embodiment of the third aspect. The specific implementation of the fuel cell can refer to the above embodiments and common knowledge in the field. Since the fuel cell adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0068] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0069] Example 1
[0070] This embodiment provides a catalyst, which is prepared by the following method:
[0071] A commercial zinc-based metal organic framework is selected and subjected to high-temperature pyrolysis in a nitrogen atmosphere at a pyrolysis temperature of 1000°C and a pyrolysis time of 2 hours to obtain a carbonized skeleton after pyrolysis. The carbonized skeleton is added to hydrochloric acid at a concentration of 15%, and mixed evenly by ultrasonic dispersion to obtain a first dispersion. Ferric chloride and methanol are added to the first dispersion, wherein the mass ratio of ferric chloride to methanol is 3:5, and dicyandiamide is added after mixing evenly, wherein the mass ratio of dicyandiamide to ferric chloride is 1:5, and after mixing evenly, it is placed in a hydrogen-nitrogen mixed atmosphere for heating treatment for 5 hours, and the heat treatment temperature is 900°C. After treatment, it is cooled to room temperature to obtain the catalyst.
[0072] This embodiment also provides a catalyst slurry, which is prepared by the following method:
[0073] The above catalyst was selected, deionized water was added for wetting, and then 5% by mass of Nafion emulsion and isopropanol were added to obtain a mixed solution, wherein the mass ratio of Nafion emulsion to isopropanol was 5:1, and the solid content of the mixed solution was controlled to be 2%. After mixing evenly, magnetic stirring was performed for 30 minutes, and then ultrasonic cell crushing was performed for 30 minutes in an ice water bath to obtain a catalyst slurry.
[0074] The present application also provides a membrane electrode, which is prepared by the following method:
[0075] A Pt / C catalyst with a Pt content of 50% was selected, deionized water was added for wetting, and then a Nafion emulsion with a mass fraction of 5% and isopropanol were added to obtain a mixed solution, wherein the mass ratio of Nafion emulsion to isopropanol was 5:1, and the solid content of the mixed solution was controlled to be 2%. After mixing evenly, magnetic stirring was performed for 30 minutes, and then ultrasonic cell crushing was used for 30 minutes in an ice water bath to obtain a catalyst ink.
[0076] The catalyst slurry is ultrasonically sprayed onto one side of a proton exchange membrane as an anode catalyst raw material, and the catalyst ink is sprayed onto the other side of a proton exchange membrane as a cathode catalyst raw material. After drying, the membrane electrode is taken out and gas diffusion layers are attached to both sides to obtain a membrane electrode.
[0077] Example 2
[0078] This embodiment provides a catalyst, which is prepared by the following method:
[0079] A commercial zinc-based metal organic framework was selected and subjected to high-temperature pyrolysis in a nitrogen atmosphere at a pyrolysis temperature of 900°C and a pyrolysis time of 2 hours to obtain a carbonized skeleton after pyrolysis. The carbonized skeleton was added to hydrochloric acid at a concentration of 15%, and mixed evenly by ultrasonic dispersion to obtain a first dispersion. Ferric chloride and methanol were added to the first dispersion, wherein the mass ratio of ferric chloride to methanol was 1:2, and dicyandiamide was added after mixing evenly, wherein the mass ratio of dicyandiamide to ferric chloride was 1:10, and after mixing evenly, it was placed in a hydrogen-nitrogen mixed atmosphere for heating treatment for 5 hours, and the heat treatment temperature was 1000°C. After treatment, it was cooled to room temperature to obtain the catalyst.
[0080] This embodiment also provides a catalyst slurry, which is prepared by the following method:
[0081] The above catalyst was selected, deionized water was added for wetting, and then 5% by mass of Nafion emulsion and isopropanol were added to obtain a mixed solution, wherein the mass ratio of Nafion emulsion to isopropanol was 5:1, and the solid content of the mixed solution was controlled to be 2%. After being mixed evenly, magnetic stirring was performed for 30 minutes, and then ultrasonic cell crushing was performed for 30 minutes in an ice water bath to obtain a catalyst slurry.
[0082] A Pt / C catalyst with a Pt content of 50% was selected, deionized water was added for wetting, and then a Nafion emulsion with a mass fraction of 5% and isopropanol were added to obtain a mixed solution, wherein the mass ratio of Nafion emulsion to isopropanol was 5:1, and the solid content of the mixed solution was controlled to be 2%. After mixing evenly, magnetic stirring was performed for 30 minutes, and then ultrasonic cell crushing was used for 30 minutes in an ice water bath to obtain a catalyst ink.
[0083] The catalyst slurry is ultrasonically sprayed onto one side of a proton exchange membrane as an anode catalyst raw material, and the catalyst ink is sprayed onto the other side of a proton exchange membrane as a cathode catalyst raw material. After drying, the membrane electrode is taken out and gas diffusion layers are attached to both sides to obtain a membrane electrode.
[0084] Comparative Example
[0085] The difference between this comparative example and Example 1 is that the catalyst used in the anode catalyst layer is different.
[0086] The catalyst slurry described in this comparative example was prepared by the following method:
[0087] A PtIr / C catalyst with a Pt content of 50% and a Pt / C catalyst with a Pt content of 50% are selected, wherein the ratio of the two can be 1:5, deionized water is added for wetting after mixing, and then a Nafion emulsion with a mass fraction of 5% and isopropanol are added to obtain a mixed solution, wherein the mass ratio of the Nafion emulsion and the isopropanol is 5:1, and the solid content of the mixed solution is controlled to be 2%. After mixing evenly, magnetic stirring is performed for 30 minutes, and then ultrasonic cell crushing is performed in an ice water bath for 30 minutes to obtain a catalyst ink.
[0088] Related experiments and effect data:
[0089] The membrane electrode obtained in the embodiment and the comparative example was tested on a single cell, and the test bench was a Qunyi 850e. Since a single cell does not reverse polarity, it is necessary to artificially force reverse polarity, and the obtained polarization curve is shown in the figure below. Figure 1As shown. After a period of time, the performance of the membrane electrode in the comparative example was significantly lost. The performance of the membrane electrode in Examples 1 and 2 also showed a certain degree of loss, but the degree of loss was much lower than that in the comparative example. It can be seen that the anti-reverse performance of Examples 1 and 2 has been significantly improved, which may be due to the better contact between the Fe nanoparticles as active anti-reverse materials and the carbon carrier.
[0090] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0091] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.
[0092] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a catalyst, It is characterized in that The preparation method of the catalyst comprises the following steps: Providing a zinc-based metal organic framework, and performing high-temperature pyrolysis on the zinc-based metal organic framework under the protection of an inert gas to obtain a carbonized framework; Adding the carbonized skeleton into hydrochloric acid and dispersing it evenly to obtain a first dispersion; Adding ferric chloride, an alcohol solvent and dicyandiamide to the first dispersion and dispersing them evenly to obtain a second dispersion; The second dispersion is heat-treated in a mixed atmosphere of hydrogen and inert gas, the carbonized skeleton is nitrogen-doped and Fe nanoparticles are generated on the carbonized skeleton to obtain the catalyst.
2. The method for preparing the catalyst according to claim 1, It is characterized in that The temperature of the high temperature pyrolysis is 900-1000°C.
3. The method for preparing the catalyst according to claim 1, It is characterized in that The high temperature pyrolysis time is 1.5 to 2.5 hours.
4. The method for preparing the catalyst according to claim 1, It is characterized in that The concentration of the hydrochloric acid is 10% to 20%.
5. The method for preparing the catalyst according to claim 1, It is characterized in that The solid content of the first dispersion is 18% to 22%.
6. The method for preparing the catalyst according to claim 1, It is characterized in that In the second dispersion, the mass ratio of ferric chloride to hydrochloric acid is 1:4-6; and / or, In the second dispersion, the mass ratio of ferric chloride to dicyandiamide is 1:5-10; and / or, In the second dispersion, the mass ratio of ferric chloride to alcohol solvent is 1:2.5-3.
7. The method for preparing the catalyst according to claim 1, It is characterized in that The heat treatment temperature is 900-1000° C.; and / or, The heat treatment time is 4 to 6 hours.
8. A catalyst slurry, It is characterized in that The catalyst slurry comprises the catalyst according to any one of claims 1 to 7, nafion and isopropanol.
9. A membrane electrode, It is characterized in that The anode catalyst layer of the membrane electrode is prepared from the catalyst slurry described in claim 8.
10. A fuel cell, It is characterized in that The fuel cell comprises the membrane electrode according to claim 9.
